Development of a threat index to manage timber production on flammable forest landscapes subject to spatial harvest constraints. Issue 3 (2nd July 2016) - Troncoso, Juan J.; Weintraub, Andrés; Martell, David L.
ABSTRACT: We develop a stand-level fire threat index and incorporate it in a mixed integer programming model that can be used to help specify strategies that will maximize the expected volume harvested from a flammable forest over a finite planning horizon, subject to adjacency constraints. The inclusion of a threat index in our objective function implicitly identifies high volume harvest blocks that are most likely to burn over the planning horizon and accelerates the harvesting of those high risk stands to reduce the likelihood that they will burn before they are harvested. We illustrate the use of our model and evaluate its performance by simulating its application to two hypothetical flammable forest landscapes that are 16, 000 hectares in size. Our results indicate that our inclusion of a threat index in our objective function produces timber harvest schedules that are better than those produced using an objective function that does not include potential fire loss measures, while satisfying harvest adjacency constraints.